2016
DOI: 10.1186/s12889-016-3700-y
|View full text |Cite
|
Sign up to set email alerts
|

Inequalities in socio-economic characteristics and health and wellbeing of men with and without disabilities: a cross-sectional analysis of the baseline wave of the Australian Longitudinal Study on Male Health

Abstract: BackgroundInternationally, men with disabilities have higher rates of social and economic disadvantage and poorer health and wellbeing than men without disabilities. No single study has provided comprehensive, population-level information about the magnitude of such differences among adult men using a well-validated instrument to measure disability.MethodsWe analysed baseline data from Ten to Men – an Australian longitudinal study of male health. Ten to Men used a stratified multi-stage cluster random sample d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
12
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 19 publications
(12 citation statements)
references
References 35 publications
(34 reference statements)
0
12
0
Order By: Relevance
“…This in turn facilitates access to factors that inherently support physical and mental health, such as housing, transport and recreation. Work helps to provide structure to people's daily lives, as well as contributing to a person's sense of self and social connectedness [20][21][22]. Previous research has also found work plays a central role in recovery by encouraging people with mental illness to develop strategies to manage their symptoms [23].…”
Section: Mental Health and Workmentioning
confidence: 99%
“…This in turn facilitates access to factors that inherently support physical and mental health, such as housing, transport and recreation. Work helps to provide structure to people's daily lives, as well as contributing to a person's sense of self and social connectedness [20][21][22]. Previous research has also found work plays a central role in recovery by encouraging people with mental illness to develop strategies to manage their symptoms [23].…”
Section: Mental Health and Workmentioning
confidence: 99%
“…As well as evidence of associations between disability and disadvantage at the individual level, there is evidence of a geographic dimension to disability-related disadvantage. Several studies have shown that people with disability tend to live in more socially disadvantaged areas than those without disability [23][24][25][26][27]. Such spatial patterning in exposure to social determinants of health, including those related to built environment characteristics, can potentially serve to exacerbate inequalities.…”
Section: Introductionmentioning
confidence: 99%
“…One aim of the Swedish public health policy is to promote conditions for good health for the entire population (Public Health Agency of Sweden, 2018). Nevertheless, it is acknowledged in Sweden, as in other countries, that people with disabilities typically have poorer health than the general population (Cooper et al, 2018;Gustavson et al, 2005;Haider et al, 2013;Kavanagh et al, 2016).…”
Section: Introductionmentioning
confidence: 99%
“…One aim of the Swedish public health policy is to promote conditions for good health for the entire population (Public Health Agency of Sweden, 2018). Nevertheless, it is acknowledged in Sweden, as in other countries, that people with disabilities typically have poorer health than the general population (Cooper et al, 2018; Gustavson et al, 2005; Haider et al, 2013; Kavanagh et al, 2016). Some health problems are due to an impairment or disease, but many are the results of environmental factors (Hsieh et al, 2015), lifestyle habits with unhealthy diets (Adolfsson, 2010) and low levels of physical activity or sedentariness (Hsieh et al, 2017; Oviedo et al, 2017).…”
Section: Introductionmentioning
confidence: 99%